They patronize herbal medicine, coincidence or planned behaviour: A case of hypertensive patients in Tamale? - Mohammed Iddrisu; Abdul Razak Doat; Abdul Malik Abdulai; Abubakari Wuni (Wiley, 2023)
Abstract Aim This study assessed, if use of herbal medicine (HM) among hypertensive patients is coincidence or planned. Design Cross‐sectional survey. Methods The study used a cross‐sectional survey for collection of data from four (4) herbal medicine clinics in the Tamale metropolis in northern Ghana. Results The final or overall regression model was significant at R2 = 0.350, F(7, 214) = 16.464, p < 0.001. No sociodemographic characteristic predicted herbal medicine use. Only religion and educational level were associated with herbal medicine use. Attitude (p = 0.002), subjective norms (p = 0.001) and behavioural intention (p = 0.000) significantly predicted HM use. Public contribution Data were collected from respondents only after they had verbally given free and informed consent to take part in the study. The results of this study therefore showed that herbal medicine use among these patients is not coincidence but planned. Health professionals by this study should appreciate the effect of religion and educational background in their health education on Herbal Medicines.